Review on Smart Electric Metering System Based on GSM/IOT - Hassan Mir, Shaista; Ashruf, Sahreen; Sameena; Bhat, Yasmeen; Beigh, Nadeem (Asian Journal of Electrical Sciences, 2019)
Arduino and GSM based smart energy meters for advanced metering and billing system is able to read and send data via wireless protocol using GSM technology through GSM modem, capable of managing the meters as well as the line connections. For GSM module uses the network coverage of the SIM. Smart Energy Meter uses SMS or/and Wi-Fi to send the power/unit data to cloud, so that user can access the data room module Apps and websites. Using cutting edge technology smart energy meters will save money, labour, efforts and time and at the same time it will effectively monitor the electricity consumption, usage and fraud. It is safe and easy to use and user friendly. The metering system uses cheap components which will decrease the overall cost of the equipment increasing its affordability and penetration in non-metered areas.